Genome-Wide Characterization of Sedum plumbizincicola HMA Gene Family Provides Functional Implications in Cadmium Response - Qingyu Huang; Wenmin Qiu; Miao Yu; Shaocui Li; Zhuchou Lu; Yue Zhu; Xianzhao Kan; Renying Zhuo (Plants, 2022)
Heavy-metal ATPase (HMA), an ancient family of transition metal pumps, plays important roles in the transmembrane transport of transition metals such as Cu, Zn, Cd, and Co. Although characterization of HMAs has been conducted in several plants, scarcely knowledge was revealed in Sedum plumbizincicola, a type of cadmium (Cd) hyperaccumulator found in Zhejiang, China. In this study, we first carried out research on genome-wide analysis of the HMA gene family in S. plumbizincicola and finally identified 8 SpHMA genes and divided them into two subfamilies according to sequence alignment and phylogenetic analysis. In addition, a structural analysis showed that SpHMAs were relatively conserved during evolution. All of the SpHMAs contained the HMA domain and the highly conserved motifs, such as DKTGT, GDGxNDxP, PxxK S/TGE, HP, and CPx/SPC. A promoter analysis showed that the majority of the SpHMA genes had cis-acting elements related to the abiotic stress response. The expression profiles showed that most SpHMAs exhibited tissue expression specificity and their expression can be regulated by different heavy metal stress. The members of Zn/Co/Cd/Pb subgroup (SpHMA1-3) were verified to be upregulated in various tissues when exposed to CdCl2. Here we also found that the expression of SpHMA7, which belonged to the Cu/Ag subgroup, had an upregulated trend in Cd stress. Overexpression of SpHMA7 in transgenic yeast indicated an improved sensitivity to Cd. These results provide insights into the evolutionary processes and potential functions of the HMA gene family in S. plumbizincicola, laying a theoretical basis for further studies on figuring out their roles in regulating plant responses to biotic/abiotic stresses.